If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y(2y + -8) = 0 Reorder the terms: y(-8 + 2y) = 0 (-8 * y + 2y * y) = 0 (-8y + 2y2) = 0 Solving -8y + 2y2 = 0 Solving for variable 'y'. Factor out the Greatest Common Factor (GCF), '2y'. 2y(-4 + y) = 0 Ignore the factor 2.Subproblem 1
Set the factor 'y' equal to zero and attempt to solve: Simplifying y = 0 Solving y = 0 Move all terms containing y to the left, all other terms to the right. Simplifying y = 0Subproblem 2
Set the factor '(-4 + y)' equal to zero and attempt to solve: Simplifying -4 + y = 0 Solving -4 + y = 0 Move all terms containing y to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + y = 0 + 4 Combine like terms: -4 + 4 = 0 0 + y = 0 + 4 y = 0 + 4 Combine like terms: 0 + 4 = 4 y = 4 Simplifying y = 4Solution
y = {0, 4}
| 3(7Y)= | | 5.4(3+2x)-4.2=12 | | 5(x-1)+3(2x-1)=3 | | 4.17x+0.94=3.7x | | 1.7(-9.7x+6)-5= | | 0.1x+0.3= | | 6x-5-1+2x-4x=66 | | 7x-8x+x-5x= | | F=(1.8*-5)+32 | | 32x=456 | | 1.5x-3=-1.5x+15 | | 4v-18=6(v-4) | | -5a-2=3(a-6) | | 760-50h=0 | | -9.7(1.7x-5)+6= | | .16x+.8(x-4)=.01(3x-2) | | 3+2x=2(2x+2)-3(x-3) | | 3(2x-6)=4(x+2) | | 2w+2(4x-7)=86 | | 7m+12/8=2m-1/3 | | 4p^2=-9p-2 | | 3x-1+x+x=6.4 | | 3(2x-6)=-4(x-2) | | c^2=33 | | -z-3.2=-22.8+3z | | 0.05(342-x)+0.07x=72 | | 2x+2(x-1)=2x-16+3x | | 3(2x-4)=-4(x-2) | | 16x^2=144-9y^2 | | (10m)/(5m) | | 4x=-2(3x-5) | | z^3-3iz^2-3z+i+1=0 |